1998
DOI: 10.2466/pr0.1998.82.1.203
|View full text |Cite
|
Sign up to set email alerts
|

Feedback, Test Anxiety and Performance in a College Course

Abstract: The effects of three forms of test feedback and text anxiety on test performance were examined within the context of a self-paced, criterion-based course in educational psychology. 73 undergraduate students completed seven units of work and were evaluated by computer-administered unit tests. Students were randomly assigned to one of three test feedback forms: (1) item-by-item knowledge of responses, (2) answer-until-correct, and (3) delayed feedback. Students received their assigned feedback during the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…Sex of participant did not differentially affect any dependent measure, supporting the absence of such differences in our prior studies, but not reports that gender influences the likelihood of changing answers and interacts with item difficulty (see Ramsey et aL, 1987) and self-reported achievement level (Hanna, 1976). Feedback did not differentially affect test-taking anxiety (see Clark, Fox, & Schneider, 1998), and neither inhibited the types of mindful behavior that permit deeper levels of understanding nor influenced learners to discontinue further interest in test items (see Bangert-Drowns, Kulik, Kulik, & Morgan, 1991). Similarly, no dependent measure was differentially affected by the source of feedback (educator, IF AT), an outcome that does not support prior reports that more learning is observed when feedback is provided by an educator (see Dihoff et aL, 2005;Sassenrath & Garverick, 1965).…”
Section: Repetition Of Inaccurate Perseverative Responding Responsessupporting
confidence: 78%
“…Sex of participant did not differentially affect any dependent measure, supporting the absence of such differences in our prior studies, but not reports that gender influences the likelihood of changing answers and interacts with item difficulty (see Ramsey et aL, 1987) and self-reported achievement level (Hanna, 1976). Feedback did not differentially affect test-taking anxiety (see Clark, Fox, & Schneider, 1998), and neither inhibited the types of mindful behavior that permit deeper levels of understanding nor influenced learners to discontinue further interest in test items (see Bangert-Drowns, Kulik, Kulik, & Morgan, 1991). Similarly, no dependent measure was differentially affected by the source of feedback (educator, IF AT), an outcome that does not support prior reports that more learning is observed when feedback is provided by an educator (see Dihoff et aL, 2005;Sassenrath & Garverick, 1965).…”
Section: Repetition Of Inaccurate Perseverative Responding Responsessupporting
confidence: 78%
“…Participants in that study were permitted to select the condition of feedback they preferred during later testing periods, and most selected the answer-until-correct format, a choice not related to self-reported level of test anxiety. The absence of a feedback effect in Clark et al (1998) is consistent with the results of the present study as is the preference for an answer-until-correct format. The results of these studies demonstrate that feedback, positive or negative, affects neither academic test performance with new items nor test anxiety.…”
Section: Discussionsupporting
confidence: 81%
“…These outcomes have not been observed in our laboratory, although these differences may be related to the assessment of projected rather than actual performance. Clark, Fox, and Schneider (1998) reported that neither delayed nor immediate feedback presented in either an item-by-item or an answer-until-correct format affected student performance, and that anxiety during testing was not related to type of feedback. Participants in that study were permitted to select the condition of feedback they preferred during later testing periods, and most selected the answer-until-correct format, a choice not related to self-reported level of test anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety level can impact test performance, [10][11][12] with test performance typically being inversely related to levels of test anxiety. [13][14][15] Despite potential anxiety, the students in this cohort did not report that the format of the examination hindered their performance. This is confirmed by consistent examination scores compared to historical controls.…”
Section: Discussionmentioning
confidence: 99%